2017
DOI: 10.1002/ejoc.201700782
|View full text |Cite
|
Sign up to set email alerts
|

A Facile One‐Pot Synthesis of 1,2,3‐Tri‐ and 1,1,2,3‐Tetrasubstituted Bis(guanidine)s from Bis(thiourea)s

Abstract: A facile and efficient one‐pot strategy for the preparation of 1,2,3‐tri‐ and 1,1,2,3‐tetrasubstituted bis(guanidine)s by starting from from readily available bis(thiourea)s has been successfully developed. The reaction provides products that contain a range of terminal and bridging groups. After a simple workup procedure, the products were obtained in analytically pure and in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…This phenomenon was earlier observed for a tetradentate ( t ‐1,2‐DACH‐)bis(amidine)[7a] and the hexadentate congener 5 . Recently, a related bis(guanidine) featuring an n ‐propylene bridge has been reported that shows inter‐ and intramolecular hydrogen bonding as well …”
Section: Resultssupporting
confidence: 61%
“…This phenomenon was earlier observed for a tetradentate ( t ‐1,2‐DACH‐)bis(amidine)[7a] and the hexadentate congener 5 . Recently, a related bis(guanidine) featuring an n ‐propylene bridge has been reported that shows inter‐ and intramolecular hydrogen bonding as well …”
Section: Resultssupporting
confidence: 61%
“…These routes give rise to bis(guanidine)s with a different degree of substitution: although using the routes i ) to iii ), di‐, tri‐, and tetra‐substituted bis(guanidine)s are accessible, on route v ), di‐ and trisubstituted bis(guanidine)s have been prepared, and for the routes iv ) and vi ), all reports known to date are limited to trisubstituted compounds (R′=R′′=H). Overall, route i ), a one‐pot reaction with a simple workup procedure, is preferential because the related bis(thiourea)s are readily available and the desulfurization agent PbO can be recycled . However, in case of ethylene‐bridged bis(thiourea)s bearing terminal alkyl groups, N ‐(alkyl)‐4,5‐dihydro‐1 H ‐imidazol‐2‐amines are obtained instead of the desired bis(guanidine)s .…”
Section: Bis(guanidine)smentioning
confidence: 99%
“…Overall, route i ), a one‐pot reaction with a simple workup procedure, is preferential because the related bis(thiourea)s are readily available and the desulfurization agent PbO can be recycled . However, in case of ethylene‐bridged bis(thiourea)s bearing terminal alkyl groups, N ‐(alkyl)‐4,5‐dihydro‐1 H ‐imidazol‐2‐amines are obtained instead of the desired bis(guanidine)s . If the terminal alkyl group is substituted by a sterically demanding aryl group, such as 2,6‐diisopropylphenyl, bis(guanidine)s are formed as a minor product, whereas 3,4‐ethylene‐bridged biguanides correspond to the main product .…”
Section: Bis(guanidine)smentioning
confidence: 99%
“…Thus, reaction of bis‐thiourea derivative 14 with 20 equiv of pyrrolidine 183 and 2.1 equiv of PbO in toluene afforded the bis‐guanidine derivative 184 via desulfurization process. Various alkyl and aryl linker groups were tolerated under the applied reaction conditions (Scheme ) .…”
Section: Reactions Of Bis‐thioureasmentioning
confidence: 99%